Shareholder Liability and Bank Failure - Felipe Aldunate; Dirk Jenter; Arthur Korteweg; Peter Koudijs (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Does enhanced shareholder liability reduce bank failure? We compare the performance of around 4,200 state-regulated banks of similar size in neighboring U.S. states with different liability regimes during the Great Depression. The distress rate of limited liability banks was 29% higher than that of banks with enhanced liability. Results are robust to a diff-in-diff analysis incorporating nationally-regulated banks (which faced the same regulations everywhere) and are not driven by other differences in state regulations, Fed membership, local characteristics, or differential selection into state-regulated banks. Our results suggest that exposing shareholders to more downside risk can successfully reduce bank failure.
Keywords: G21; G28; G32; N22; 330; limited liability; bank risk taking; financial crises; Great Depression